PENGARUH PEMAKAIAN BEBERAPA JENIS DAUN TUMBUHAN TERHADAP PERTUMBUHAN Sitophilus oryzae L. PADA BERAS (Oryza sativa L.) - Sari, Desyulita; Lusi, Armein; Safitri, Elza (STKIP PGRI Sumbar, 2014)
ABSTRACT Rice is the main food as a source of carbohydrates for most of Indonesian society. Farmers at harvest usually storing rice warehouse. During the storage period of rice will be damaged and shrinkage both in quality and quantity. One cause of the decline in the quality and quantity of stored corps from pest attack is a warehouse. One of the pests that attack warehouse is Sitophilus oryzae L. (Rice beetle). This study aims to determine the effect of the use of several of leaves of plants on the development of Sitophilus oryzae L. in rice (Oryza sativa). This research has been carried out in November to December 2013 Laboratory Biology Education Courses STKIP PGRI West Sumatra. This study used a Completely Randomized Design (CRD) with 5 treatments and 3 replication. As treatments is A (Control/No leaves), B (Bay leaf), C (Sugar apple leaves), D (Soursop leaf) and E (Red betel leaf). Observed data, that is namely mortality, imago population of Sitophilus oryzae and the percentage of damage caused by the attack of rice Sitophilus oryzae. The data were analyzed by analysis of variance with least significant difference test further (LSD) at the 5% level. The results shomed that the use of some types of plants that bay leaf (Syzygium polyanthum), sugar apple leaves (Annona squamosa), soursop leaf (Annona muricata), red betel leaf (Piper crocatum) significant effect on mortality, Sitophilus oryzae imago population and the percentage of damage caused by the attack of rice Sitophilus oryzae. The leaves are most effective for controlling Sitophilus oryzae attack is red betel leaf (Piper crocatum).